Neurophthalmologic and Orthoptic Ambulatory Assessments Reveal Ocular and Visual Changes in Patients With Early Alzheimer and Parkinson's Disease - Bargagli, Alessia; Fontanelli, Enrica; Zanca, Dario; Castelli, Ilaria; Rosini, Francesca; Maddii, Silvia; Di Donato, Ilaria; Carluccio, Alessandra; Battisti, Carla; Tosi, Gian M.; Dotti, Maria T.; Rufa, Alessandra (Frontiers in Neurology, 2020)
Patients with Alzheimer’s disease and Parkinson’s disease develop a progressive decline of visual function. This condition aggravate overall cognitive and motor abilities, is a risk factor for developing hallucinations and can have a signiﬁcant inﬂuence on general quality of life. Visual problems are commonly complained by patients with PD and AD in early stages of the disease, but also in normal ageing, making it difficult to differentiate between normal and pathological conditions. In this respect, their real incidence has remained largely underestimated and no rehabilitative approaches have been standardized. With the aim to increase awareness for ocular and visual disorders, easily assessable in an outpatient setting, we collected the main neurophthalmologic and orthoptic parameters including OCT in six patients with a diagnosis of PD, six patients with a diagnosis of early AD and eight control subjects. We also evaluated the patient’s ability to recognize changes in facial expression. Our study demonstrates that visual problems including blurred vision, diplopia, reading discomfort, photophobia and glare are commonly reported in patients with PD and AD. Moreover, abnormal eye alignment and vergence insufficiency were documented in all patients during examination. Despite the small size of the sample we demonstrated a greater ganglion cells and RNFL damage and a defect of facial emotion recognition, in AD/PD patients with respect to a comparable group of normal elderly, with peculiarities depending upon the disease. Ocular defects or visual discomfort could be correctly evaluated in these patients and possibly corrected by means of lens, orthoptic exercises, and visual rehabilitation. Such a practical approach may help to ameliorate motor autonomy, reading ability and may also reduce the risk of falls, with a positive impact in daily living activities.